Teknik Konseling Islami Dalam Menangani Masalah Peserta Didik Di Era Kontemporer - Hudamahya, Aulia (Prodi Pendidikan Keagamaan Islam, 2025)
This article discusses the application of the tazkiyatun nafs technique as an Islamic counseling approach to addressing students' issues. This technique, rooted in Islamic tradition, emphasizes the purification of the soul through the process of self-reflection (muhasabah), dhikr, and prayer. This research uses a literature study method by analyzing various related literature to identify the effectiveness of this technique in helping students overcome emotional pressure, improve social relationships, and enhance spiritual quality. The study results indicate that this technique can provide holistic and relevant solutions to addressing the challenges of modern education. Thus, tazkiyatun nafs can be an effective alternative in Islamic counseling practices within educational settings.